Urban park system on public health: underlying driving mechanism and planning thinking - Zhang, Cheng; Su, Qin; Zhu, Yanqun (Frontiers in Public Health, 2023)
Urban parks are one of the major outdoor public spaces, and the quality of their environment is closely related to the public health of residents. The quality of the park environment is one of the important factors affecting urban residents' use of parks. Good air quality, comfortable thermal environment, and appropriate scale of activity space in parks contribute to the physical and mental health of residents; in addition, a high-quality urban park environment helps to increase the frequency of outdoor activities of residents and enhance the vitality of cities. In order to effectively play the role of urban park system in promoting urban residents' health, this manuscript studies the coupling relationship between "urban park system" and "public health system" by constructing a coordination model, applying AHP hierarchical analysis to the comprehensive evaluation of public space, analyzing the weighting relationship of evaluation factors, improving the evaluation efficiency, revealing the dynamic mechanism of urban park system affecting the benign development of public health It also clarifies the positive contribution of urban parks to public health, and helps to incorporate more citizens' expectations when planning and designing public spaces in the future, which allows existing projects to be monitored and followed up, and more importantly, serves as a reference for future planning. Finally, based on the analysis results, this manuscript considers the optimal development strategies of urban parks at macro and micro levels to promote the sustainable development of urban public health.